Toward the Understanding of Topographical and Spectral Signatures of Infant Movement Artifacts in Naturalistic EEG - Georgieva, Stanimira; Lester, Suzannah; Noreika, Valdas; Yilmaz, Meryem Nazli; Wass, Sam; Leong, Victoria (Frontiers in Neuroscience, 2020)
Electroencephalography (EEG) is perhaps the most widely used brain-imaging technique for paediatric populations. However, EEG signals are prone to distortion by motion. Compared to adults, infants’ motion is both more frequent and less stereotypical yet motion effects on the infant EEG signal are largely undocumented. Here, we present a systematic assessment of naturalistic motion effects on the infant EEG signal. EEG recordings were performed with 14 infants (12 analysed) who passively-watched movies whilst spontaneously producing periods of bodily movement and rest. Each infant produced an average of 38.3s (SD=14.7s) of rest and 18.8s (SD=17.9s) of single motion segments for the final analysis. Five types of infant motions were analysed: Jaw movements, and Limb Movements of the Hand, Arm, Foot and Leg. Significant movement-related distortions of the EEG signal were detected using cluster-based permutation analysis. This analysis revealed that, relative to resting state, infants’ Jaw and Arm movements produced significant increases in beta (~15 Hz) power, particularly over peripheral sites. Jaw movements also produced more anteriorly-located effects than Arm movements, which were most pronounced over posterior parietal and occipital sites. The cluster analysis also revealed trends toward decreased power in the theta and alpha bands observed over central topographies for all motion types. However, given the very limited quantity of infant data in this study, caution is recommended in interpreting these findings before subsequent replications are conducted. Nonetheless, this work is an important first step to inform future development of methods for addressing EEG motion-related artifacts and support wider use of naturalistic paradigms in social and developmental neuroscience.